Prehospital Volume Therapy as an Independent Risk Factor after Trauma. (9th April 2015) - Hussmann, Bjoern; Heuer, Matthias; Lefering, Rolf; Touma, Alexander; Schoeneberg, Carsten; Keitel, Judith; Lendemans, Sven
Abstract : Background . Prehospital volume therapy remains widely used after trauma, while evidence regarding its disadvantages is growing. The primary objective of this study was to investigate the volume administered in a prehospital setting as an independent risk factor for mortality. Material and Methods . Patients who met the following criteria were analyzed retrospectively: Injury Severity Score = 16, primary admission (between 2002 and 2010), and age = 16 years. The following data had to be available: volume administered (including packed red cells), blood pressure, Glasgow Coma Scale, therapeutic measures, and laboratory results. Following a univariate analysis, independent risk factors for mortality after trauma were investigated using a multivariate regression analysis. Results . A collective of 7, 641 patients met the inclusion criteria, showing that increasing volumes administered in a prehospital setting were an independent risk factor for mortality (odds ratio: 1.34). This tendency was even more pronounced in patients without severe traumatic brain injury (TBI) (odds ratio: 2.71), while the opposite tendency was observed in patients with TBI. Conclusions . Prehospital volume therapy in patients without severe TBI represents an independent risk factor for mortality. In such cases, respiratory and circulatory conditions should be stabilized during permissive hypotension, and patient transfer should not be delayed.